PEMBERHENTIAN PNS AKIBAT PENYALAHGUNAAN WEWENANG BERDASARKAN UU NO. 20 TAHUN 2023 (STUDI PUTUSAN NO. 39 K/TUN/2023): Dismissal Of Civil Servants For Abuse Of Authority Based On Law No. 20 Of 2023 (Study Of Decision No. 39k/Tun/2023) - Rayshe Gabriela Rumbewas; Ninuk Wijiningsih (Reformasi Hukum Trisakti, 2025)
The State Civil Apparatus (ASN) is appointed by the state to support the implementation of government programs for public welfare, guided by the principles of honesty, professionalism, and competence. However, in practice, there are still ASN members who abuse their positions, highlighting the need for appropriate legal enforcement. This article examines two main issues: (1) whether the dismissal process of a civil servant from the Land Office of Semarang City complies with Law No. 20 of 2023 on State Civil Apparatus; and (2) how the implementation of Decision No. 39/K/TUN/2023 affects said civil servant. The research applies a normative legal method, analyzing disciplinary violations based on Law No. 20 of 2023 and Government Regulation No. 94 of 2021. The findings indicate that the dismissal process of Wahyudi was conducted in accordance with legal procedures, including proper summoning and examination stages. The study concludes that the disciplinary action taken was lawful and justified, representing a valid enforcement of civil servant discipline. This research provides a clear understanding of the legal mechanism and procedural standards for dismissing ASN in Indonesia, reinforcing the importance of accountability and integrity within the state apparatus.